Sports as a Middle Way: a Philosophical Analysis of the Concept of Taoism (Wu Wei) in Physical Education - Aprilius Bayu; Mu’arifin Mu’arifin; Lalu Moh Yudha Isnaini (Journal of Physical Education and Health Science, 2025)
Physical education in practice is still heavily influenced by a competitive and performance-oriented paradigm, which often neglects the philosophical and humanitarian dimensions of the learning process. This situation has the potential to cause physical and psychological stress for students, thus suboptimally achieving the goal of physical education as a means of developing a holistic human being. Based on these issues, this study aims to analyze the relevance of the Wu Wei principle in Taoist philosophy as an alternative philosophical foundation for physical education in a modern pedagogical context. This study uses a qualitative approach with a library research design, which examines classic Taoist texts, particularly the Tao Te Ching, as well as various academic literature discussing the philosophy of education, physical education, and contemporary sports pedagogy. Data are analyzed through content analysis and a philosophical hermeneutic approach to interpret the meaning of Wu Wei and its implications for physical education learning practices. The results of the study indicate that the dominance of the competitive paradigm in physical education is correlated with the emergence of burnout phenomena, decreased motivation, and neglected mental well-being of students. Conversely, a learning approach that emphasizes movement awareness, balance, and non-competitive activities in line with the Wu Wei principle has the potential to strengthen humanistic values, improve psychological well-being, and create a more meaningful learning experience. This study concludes that the integration of Wu Wei principles can serve as an alternative philosophical framework for developing a more humanistic, balanced physical education that is oriented toward character building and harmony between body, mind, and environment.